Integrated Corporate Communication to Enhance Sustainability Credibility in Green Loan Applications: A Case Study in the Oil and Gas Industry - Fannisha; Doho, Yohannes Don Bosco (Ilomata International Journal of Social Science, 2025)
This study examines how Integrated Corporate Communication (ICC) strategies shape the credibility of oil and gas companies in securing green loans, responding to growing financial sector demands for transparency and sustainability in the context of global climate action. Focusing on Company X and its interactions with Bank Y, the research addresses how ICC implementation influences perceived eligibility for green financing. By integrating the Competing Values Framework for Corporate Communication (CVFCC) with the Elaboration Likelihood Model (ELM), this study offers novel insights into the underexplored intersection of corporate communication and green financing, particularly in emerging markets where prior studies have often neglected the strategic role of ICC. Employing a qualitative case study grounded in a constructivist paradigm, data were gathered through in-depth interviews with Company X’s communication and sustainability teams and Bank Y officials, complemented by document analysis. The findings reveal that cross-functional communication spanning employee, media, investor, and government relations significantly strengthens sustainability credibility, with both central and peripheral communication strategies proving persuasive in loan assessments. The study concludes that cohesive and transparent ICC enhances the perceived credibility of energy firms, underscoring its vital role as a strategic tool for companies seeking access to sustainable finance in an increasingly scrutinised business environment.